An evaluation of fungus Piriformospora indica effects on some morphophysiological traits of valerine under drought stress - Mehdi Ghabooli; Sheida Lorestani; Zahra Movahedi; Rouholah Karimi (فیزیولوژی محیطی گیاهی, 2018)
We designed a set of comparative experiments to study the impact of inoculation with different inoculum of P. indica (non-inoculated, inoculated with spore and mycelium of P. indica) on some morphophysiological traits of Valeriana plant under different drought stress levels [Filed capacity (F.C.) and 50% F.C.]. The experiment was conducted as a factorial experiment in a completely randomized design with three replications. The results indicated that P.indica increased the biomass of inoculated plants compared with control plants in different levels of drought stress, as in inoculated plants under drought stress total shoot and root dry weight were increased by 37% and 14%, respectively. Under stress conditions, physiological traits like as total chlorophyll (24%), total phenol (14%), carbohydrate (4.3 times), protein (17%) and proline (2.1 times) were increased in inoculated plants. Beside, inoculation with fungus decreased ionic leakage by 38%. According to the results, it seems that valerian is also one of the hosts of this fungus and potential effect of fungus on increasing of growth and stress tolerance provide further investigation of the effect of fungus on increasing of medicinal ingredient.